The Problematic Concept of Native Speaker in Psycholinguistics: Replacing Vague and Harmful Terminology With Inclusive and Accurate Measures - Cheng, Lauretta S. P.; Burgess, Danielle; Vernooij, Natasha; Solís-Barroso, Cecilia; McDermott, Ashley; Namboodiripad, Savithry (Frontiers in Psychology, 2021)
Though the term NATIVE SPEAKER/SIGNER is frequently used in language research, it is inconsistently conceptualized. Factors such as age, order, and context of acquisition, in addition to social/cultural identity, are often differentially conflated. While the ambiguity and harmful consequences of the term NATIVE SPEAKER have been problematized across disciplines, much of this literature attempts to repurpose the term in order to include and/or exclude certain populations. This paper problematizes NATIVE SPEAKER within psycholinguistics, arguing that the term is both unhelpful to rigorous theory construction and harmful to marginalized populations by reproducing normative assumptions about behavior, experience, and identity. We propose that language researchers avoid NATIVE SPEAKER altogether, and we suggest alternate ways of characterizing language experience/use. The vagueness of NATIVE SPEAKER can create problems in research design (e.g., through systematically excluding certain populations), recruitment (as participants’ definitions might diverge from researchers’), and analysis (by distilling continuous factors into under-specified binary categories). This can result in barriers to cross-study comparison, which is particularly concerning for theory construction and replicability. From a research ethics perspective, it matters how participants are characterized and included: Excluding participants based on binary/essentialist conceptualizations of nativeness upholds deficit perspectives towards multilingualism and non-hegemonic modes of language acquisition. Finally, by implicitly assuming the existence of a critical period, NATIVE SPEAKER brings with it theoretical baggage which not all researchers may want to carry. Given the issues above and how ‘nativeness’ is racialized (particularly in European and North American contexts), we ask that researchers consider carefully whether exclusion of marginalized/minoritized populations is necessary or justified—particularly when NATIVE SPEAKER is used only as a way to achieve linguistic homogeneity. Instead, we urge psycholinguists to explicitly state the specific axes traditionally implied by NATIVENESS that they wish to target. We outline several of these (e.g., order of acquisition, allegiance, comfort with providing intuitions), and give examples of how to recruit and describe participants while eschewing NATIVE SPEAKER. Shifting away from harmful conventions such as NATIVE SPEAKER will not only improve research design and analysis, but is also one way we can co-create a more just and inclusive field.